Anti-Inflammatory and Antiarthritic Activity of Anthraquinone Derivatives in Rodents - Ajay D. Kshirsagar; Prashant V. Panchal; Uday N. Harle; Rabindra K. Nanda; Haidarali M. Shaikh (International Journal of Inflammation)
Aloe emodin is isolated compound of aloe vera which is used traditionally as an anti-inflammatory agent. In vitro pharmacokinetic data suggest that glucuronosyl or sulfated forms of aloe emodin may provide some limitations in its absorption capacity. Aloe emodin was reported to have in vitro anti-inflammatory activity due to inhibition of inducible nitric oxide (iNO) and prostaglandin E2, via its action on murine macrophages. However, present work evidenced that molecular docking of aloe emodin modulates the anti-inflammatory activity, as well as expression of COX-2 (cyclooxygenase-2) in rodent. The AEC (4,5-dihydroxy-9,10-dioxo-9,10-dihydroanthracene-2 carboxylic acid) was synthesized using aloe emodin as starting material. The study was planned for evaluation of possible anti-inflammatory and antiarthritic activity in carrageenan rat induced paw oedema and complete Freund’s adjuvant induced arthritis in rats. The AE (aloe emodin) and AEC significantly P<0.001 reduced carrageenan induced paw edema at 50 and 75 mg/kg. Complete Freund’s adjuvant induced arthritis model showed significant P<0.001 decrease in injected and noninjected paw volume, arthritic score. AE and AEC showed significant effect on various biochemical, antioxidant, and hematological parameters. Diclofenac sodium 10 mg/kg showed significant P<0.001 inhibition in inflammation and arthritis.